Vol 2 no 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: SISTEM PENGELOLAAN DANA DESA DALAM PERSPEKTIF EKONOMI SYARIAH (Studi Kasus di Desa Kebondalem Kecamatan Bejen Kabupaten Temanggung) - KURDI, SULAEMAN (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
Dana Desa is a fund sourced from the State Budget intended for villages that is transferred through the District or City Regional Revenue and Expenditure Budget which is rolled out for villages to finance governance, development implementation, community development and empowerment. This study aims to find out how to plan, implement and manage Dana Desa. In addition, this study aims to determine the efforts made by the village government in improving community empowerment. Furthermore, to find out how the implementation, reporting and accountability of Dana Desa are viewed from the perspective of sharia economics. This research is a qualitative research with the main aim to descriptive or describe in detail and in depth the process of implementing Dana Desa so that they can provide roles / contributions as expected by the central government. The data collection techniques used are free guided interview methods, observation and documentation. After the researcher collects the data, the next step is data analysis. The analysis that researchers do uses two ways, namely processing the initial data and classifying it and the next stage of the data to be analyzed The management of Dana Desa in Kebondalem village is in accordance with the regulations contained in Perbub No. 72 of 2021 concerning Village Development Planning Guidelines. However, if viewed from the perspective of Sharia Economics, it is not fully appropriate, it can be seen that there are still activities that are funded every year with Dana Desa but only a few people feel the benefits